Small doubling, atomic structure and $\ell$-divisible set families - Lior Gishboliner; Benny Sudakov; Istvan Tomon (Discrete Analysis, 2022)
Small doubling, atomic structure and $\ell$-divisible set families, Discrete Analysis 2022:11, 16 pp.